Food in the Civil War era : the North - Veit, Helen Zoe (American food in history., 2014)
Cookbooks offer a unique and valuable way to examine American life. Their lessons, however, are not always obvious. Direct references to the American Civil War were rare in cookbooks, even in those published right in the middle of it. In part, this is a reminder that lives went on and that dinner still appeared on most tables most nights, no matter how much the world was changing outside. But people accustomed to thinking of cookbooks as a source for recipes, and not much else, can be surprised by how much information they can reveal about the daily lives and ways of thinking of the people wh.